Study About The Robustness Of The Bayesian Criterion - بدر دريد حسين (Journal of Economics and Administrative Sciences, 2024)
In this research work an attempt has been made to investigate about the Robustness of the Bayesian Information criterion to estimate the order of the autoregressive process when the error of this model, Submits to a specific distributions and different cases of the time series on various size of samples by using the simulation, This criterion has been studied by depending on ten distributions, they are (Normal, log-Normal, continues uniform, Gamma , Exponential, Gamble, Cauchy, Poisson, Binomial, Discrete uniform) distributions, and then it has been reached to many collection and recommendations related to this object , when the series residual variable is subject to each ( Poisson , Binomial , Exponential , Discrete uniform , continues uniform, log-Normal ) distributions , then robust Bayesian criterion to estimate the order of the autoregressive process high if the Non- stationary Time , began decreases as the sample size increases those subject to a random path and when the series residual variable is subject to each they are (Gamma, Gamble, Cauchy ) distributions then robust Bayesian criterion if the decreases as the sample size at Non- stationary Time Series and increases as the sample size increases, and the greater robust the size of the sample of those subject to a random path .